2015
DOI: 10.1017/s1751731114002791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporating sugar beet pulp in the finisher diet on performance of geese

Abstract: The aim of this work was to study the effects of incorporating sugar beet pulp (SBP) into the diet on the development of the crop and performance of geese. A total of 480 1-day-old ganders were divided into three groups differing in the composition and mode of distribution of the diet offered from day 56 to 89. The following two diets were used: a standard diet (nitrogen-corrected apparent metabolizable energy, AMEn 11.44 MJ/kg; 160 g/kg CP) or a diet containing 10% of SBP (SBP diet; AMEn 11.47 MJ/kg; 160 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…This is not consistent with the results of Arroyo et al (2015) who showed a decreased feed intake (−7%) and no effect on the BW using the same SBP incorporation level. On the other hand, geese submitted to the loose-mix feeding system were not significantly heavier than geese fed a complete pelleted diet at the end of the rearing period, as previously shown by Arroyo et al (2012a,b and2013b).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is not consistent with the results of Arroyo et al (2015) who showed a decreased feed intake (−7%) and no effect on the BW using the same SBP incorporation level. On the other hand, geese submitted to the loose-mix feeding system were not significantly heavier than geese fed a complete pelleted diet at the end of the rearing period, as previously shown by Arroyo et al (2012a,b and2013b).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we observed a strong relationship between WHC of the pelleted diet intake and the crop volume at the end of the growing period, as previously shown (Arroyo et al, 2012a;Arroyo et al, 2015). However, we observed no link between crop volume and mortality rate during the overfeeding period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We recommend performing both measurements routinely because they have different meanings. For example, WHC seems more relevant to deal with issues such as litter quality in poultry (Ouhida et al, 2000), while SC seems more suited to solve the issues of crop expansion in waterfowl (Arroyo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%